2019
DOI: 10.1002/ieam.4123
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity studies used in registration, evaluation, authorisation and restriction of chemicals (REACH): How accurately are they reported?

Abstract: Toxicity studies on chemicals registered under the European Union's Registration, Evaluation, Authorisation and Restriction of Chemicals (REACH) regulation are provided as summaries instead of as a full study report. Because the registration data are used by regulatory agencies to identify chemicals of concern, the study summaries must accurately reflect the information in studies. A “study summary” should include sufficient information on the objectives, methods, results, and conclusions in the full study rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Large studies (mainly focusing on animal experimentation) have reported that test method descriptions are often poor (Freedman et al, 2015;Hair et al, 2019;Vogt et al, 2016;Ingre-Khans et al, 2019). This lack of test method transparency may contribute significantly to reproducibility issues often reported for biomedical research (Ioannidis, 2012;Begley and Ellis, 2012;Prinz et al, 2011;Hartung et al, 2019).…”
Section: 4mentioning
confidence: 99%
“…Large studies (mainly focusing on animal experimentation) have reported that test method descriptions are often poor (Freedman et al, 2015;Hair et al, 2019;Vogt et al, 2016;Ingre-Khans et al, 2019). This lack of test method transparency may contribute significantly to reproducibility issues often reported for biomedical research (Ioannidis, 2012;Begley and Ellis, 2012;Prinz et al, 2011;Hartung et al, 2019).…”
Section: 4mentioning
confidence: 99%
“…However, using study summaries instead of full study reports can have implications for the risk assessment. Study summaries submitted by the registrants were shown to be inconsistent or incomplete concerning the reporting of information about the study design, results, and interpretation of the results [59]. Also, the evaluation and reporting of the reliability and relevance of key studies in study summaries lacked structure and transparency [56].…”
Section: Introductionmentioning
confidence: 99%